Riding the Regulatory Wave: Reflections on Recent Explorations of the Statutory and Nonstatutory Nonprofit Regulatory Cycles in 16 Jurisdictions. (August 2019) - Breen, Oonagh B.; Dunn, Alison; Sidel, Mark
This article explores both state-based regulation and self-regulation, shared narratives, and lessons to better understand the interaction of these two forms of regulation in the nonprofit space. "The Context" section outlines six preliminary research questions that inform the work. "The Framework" section then outlines the regulatory framework, focusing on various regulatory motivations, before "The Findings" section turns to country findings. In unpacking some of the major findings, we look first at state perspectives on the role of regulation before considering the sector's perspective. Taking both on board enables us to configure the relationship spectrum between state and sector when it comes to regulation and to begin to identify, based on the 16 case studies undertaken, the most common triggers for regulatory change identified therein and to reframe them through the development of a series of five regulatory propositions and seven environmental variables to help understand how different forms of regulation are triggered and interact.